Evolving paradigms in aesthetic preference: from classical philosophy to experimental aesthetics - Yahaya, Mohd Faiz; Yanfeng, H. U.; Ramli, Saiful Hasley; Yulin, H. S. U. (MAK HILL Publications, 2024)
This research focuses on the relationship between aesthetic theory and aesthetic preference, exploring the history of aesthetic theory and perspectives on aesthetic preference in product design, such as views of beauty in classical Greek philosophy, shifts in aesthetic thinking in contemporary cognitive psychology, aesthetic criteria for product design in psychophysics and experimental aesthetics, as well as aesthetic models for testing aesthetic preference. This study aims to understand the concepts of beauty and art under the influence of different historical contexts and finally, to find some suitable models for testing aesthetic preferences in product design. In the process of literature collection, a systematic review and evaluation of the development of aesthetic theory. This study provides a theoretical basis for testing aesthetic preferences in product design and makes readers more clearly recognize the factors that affect aesthetic evaluation.